Are traded forest tree seeds a potential source of nonnative pests?. Issue 7 (30th July 2019) - Franić, Iva; Prospero, Simone; Hartmann, Martin; Allan, Eric; Auger‐Rozenberg, Marie‐Anne; Grünwald, Niklaus J.; Kenis, Marc; Roques, Alain; Schneider, Salome; Sniezko, Richard; Williams, Wyatt; Eschen, René
Abstract: The international seed trade is considered relatively safe from a phytosanitary point of view and is therefore less regulated than trade in other plants for planting. However, the pests carried by traded seeds are not well known. We assessed insects and fungi in 58 traded seed lots of 11 gymnosperm and angiosperm tree species from North America, Europe, and Asia. Insects were detected by X‐raying and molecular methods. The fungal community was characterized using high‐throughput sequencing (HTS) and by growing fungi on non‐selective agar. About 30% of the seed lots contained insect larvae. Gymnosperms contained mostly hymenopteran ( Megastigmus spp.) and dipteran (Cecidomyiidae) larvae, while angiosperms contained lepidopteran ( Cydia latiferreana ) and coleopteran ( Curculio spp.) larvae. HTS indicated the presence of fungi in all seed lots and fungi grew on non‐selective agar from 96% of the seed lots. Fungal abundance and diversity were much higher than insect diversity and abundance, especially in angiosperm seeds. Almost 50% of all fungal exact sequence variants (ESVs) found in angiosperms were potential pathogens, in comparison with around 30% of potentially pathogenic ESVs found in gymnosperms. The results of this study indicate that seeds may pose a greater risk of pest introduction than previously believed or accounted for. A rapid risk assessment suggests that only a small number of species identified in this study is of phytosanitary concern. However, more research is needed to enable better risk assessment, especially to increase knowledge about the potential for transmission of fungi to seedlings and the host range and impact of identified species.